SMART LICENSE PLATE RECOGNITION SYSTEM BASED ON IMAGE PROCESSING USING NEURAL NETWORK - Koval, V.; Turchenko, V.; Kochan, V.; Sachenko, A.; Markowsky, G. (International Journal of Computing, 2014)
This paper describes the Smart Vehicle Screening System, which can be installed into a tollbooth for automated recognition of vehicle license plate information using a photograph of a vehicle. An automated system could then be implemented to control the payment of fees, parking areas, highways, bridges or tunnels, etc. There are considered an approach to identify vehicle through recognizing of it license plate using image fusion, neural networks and threshold techniques as well as some experimental results to recognize the license plate successfully.